Evolution, scripture, and science: selected writings$nB. B. Warfield ; edited and with an introduction by Mark A. Noll & David N. Livingstone - Warfield, Benjamin Breckinridge (Wipf & Stock, 2019)
Warfield on Scripture : "The divine and human in the Bible" -- Warfield on evolution and science : Review of Matheson et al., Christianity and evolution ; Review of Watts, The reign of causality ; Review of McCosh, The religious aspect of evolution ; "Charles Darwin's religious life" ; Review of Dallinger, The creator ; "Evolution or development ; "Darwin's arguments against Christianity and against religion" ; Review of Dawson, Modern ideas of evolution: as related to revelation and science ; Review of Warring, Genesis I and modern science ; Review of Shaler, The interpretation of nature ; Review of Calderwood, Evolution and man's place in nature ; Review of Iverach, Christianity and evolution ; Review of Hutton, "The ascent of man" ; Review of Watts, Drummond's "Ascent of man" ; "The present-day conception of evolution" ; Review of Tyler, The whence and wither of man ; Review of Romanes, Darwin and after Darwin ; Review of Foster, Creation ; Review of Dawson, Eden lost and won ; Review of Townsend, Evolution or creation ; Review of White, History of the warfare of science and theology ; Review of Hubrecht, The descent of the primates ; Review of Elder, Ideas from nature ; Review of Kuyper, Evolutie ; Review of MacDill, Common sense applied to Darwinism ; Review of Pfleiderer, evolution and theology ; Review of Bavinck, Schepping of Ontwikkeling ; "Creation, evolution, and mediate creation" ; "The manner and time of man's origin" ; Review of Orr, God's image in man ; Review of Kellogg, Darwinism today ; Review of Paulin, No struggle for existence ; Review of Otto, Naturalism and religion ; Review of Hastings, Encyclopaedia of religion and ethics ; "On the antiquity and the unity of the human race" ; Review of Robinson, The Christian doctrine of man ; "Calvin's doctrine of the creation" ; Review of Shearman, The natural theology of evolution ; Review of Visscher,